How do you simplify 2(a+3) + 4 (a-2)?

1 Answer
Mar 4, 2018

6a-2

Explanation:

As with any equation we want to simplify, we always expand brackets first.

color(red)(2)(color(green)(a+color(red)(3))+color(red)(4)(color(green)(a)color(red)(-2))

color(red)(2)xxcolor(green)(a)=color(green)(2a)

color(red)(2xx3)=color(red)(6)

color(red)(4)xxcolor(green)(a)=color(green)(4a)

color(red)(4xx-2)=color(red)(-8)

Therefore this turns to:

color(green)(2a+4a)+color(red)(6-8)

Collecting like terms:

color(green)(2a+4a=6a)

color(red)(6-8=-2)

This turns to:

color(green)(6a)color(red)(-2)

therefore The answer is 6a-2